Bring the girl home: surviving domestic violence and kidnapping - Wilson, Rebecca (E.P. House, 2024)
"In "Bring the Girl Home: Surviving Domestic Violence and an International Kidnapping," acclaimed author and advocate Rebecca Wilson shares her harrowing story of resilience, hope, and the relentless pursuit to reunite with her daughter. With unflinching honesty and raw emotion, Rebecca sheds light on the dark reality of abuse and the devastating impact it has on individuals and families. Through her powerful narrative, she breaks the silence and stigma surrounding domestic violence, inspiring others to find their strength and break free from the cycle of violence. As a leading voice in the fight against domestic violence and familial kidnapping, Rebecca firmly believes in the power of education, community engagement, and open dialogue."--Amazon